Pengaruh Leverage, Likuiditas, Struktur Modal Dan Ukuran Perusahaan Terhadap Kinerja Keuangan - Devi Oktaviyana; Kartika Hendra Titisari; Sari Kurniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The company's financial performance is used to measure the level of success in running a business to gain profit. This study aims to examine and analyze the effect of leverage, liquidity, capital structure and company size on financial performance. The population used is manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) for 2017-2021. Sampling by purposive sampling technique based on predetermined criteria. The method used is a quantitative method using secondary data in the form of the company's annual financial statements. In this study, 31 companies were sampled and the observation period was from 2017 to 2021. Multiple linear analysis was used in the data analysis process. The findings of this study indicate that firm size and leverage have an effect on financial performance. While those that do not affect financial performance are liquidity and capital structure. Various parties can use this research as material for consideration in assessing factors that can affect a company's financial performance as well as material for consideration by investors in making investment decisions. Keyword: Leverage, Liquidity, Capital Structure, Company Size, Perfomance Finance